2021
DOI: 10.1038/s41598-021-00102-2
|View full text |Cite
|
Sign up to set email alerts
|

Dopant activation process in Mg-implanted GaN studied by monoenergetic positron beam

Abstract: A process for activating Mg and its relationship with vacancy-type defects in Mg-implanted GaN were studied by positron annihilation spectroscopy. Mg+ ions were implanted with an energy of 10 keV, and the Mg concentration in the subsurface region (≤ 50 nm) was on the order of 1019 cm−3. After the Mg-implantation, N+ ions were implanted to provide a 300-nm-deep box profile with a N concentration of 6 × 1018 cm−3. From capacitance–voltage measurements, the sequential implantation of N was found to enhance the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…3(b)] (similar like in VD-MOSFET, see Ref. 40). On the other hand, in the second scenario, the spreading of the current from the channel region into the drift region starts at the end of the depletion region surrounding the p-type regions [see line 2 in Fig.…”
Section: Grid-spacing Of the P-n Junctionsmentioning
confidence: 69%
See 1 more Smart Citation
“…3(b)] (similar like in VD-MOSFET, see Ref. 40). On the other hand, in the second scenario, the spreading of the current from the channel region into the drift region starts at the end of the depletion region surrounding the p-type regions [see line 2 in Fig.…”
Section: Grid-spacing Of the P-n Junctionsmentioning
confidence: 69%
“…After the ion implantation process and mask removal, the faceto-face UHPA process was conducted under a N 2 pressure of 500 MPa at temperature of 1300 °C for 30 min at JUTEM. After UHPA process, we found that the experimental Mgdepth profile determined from secondary ion mass spectrometry (SIMS) extended more deeply in the GaN bulk than those predicted by MC simulations probably due to the Mg defect-assisted vertical diffusion 40,44,45) (see Fig. 8(b).…”
Section: Fabrication Process and Mg Distribution In Jbs Diodementioning
confidence: 90%
“…The same conclusion for Mg‐, H‐, and N‐implanted GaN before annealing was reported in refs. [32,36–39]. After annealing at 1000−1100 °C, the ( S , W ) value shifts to the right‐hand side and locates on the line connecting the ( S , W ) value for defect‐free GaN and ( V Ga V N ) 3 .…”
Section: Resultsmentioning
confidence: 92%
“…This suggests that the formation of Mg and H complexes is suppressed in this region. From annealing experiments for N‐implanted GaN, [ 39 ] it was found that N‐implantation decreased the size of vacancy clusters above 1200 °C annealing. This fact was attributed to the decrease in the number of V N due to the recombination between V N and excess N atoms.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the formation of Mg and H complexes is suppressed in this region. From annealing experiments for N-implanted GaN, 32 it was found that N-implantation decreased the size of vacancy clusters above 1200°C annealing. This fact was attributed to the decrease in the number of V N due to the recombination between V N and excess N atoms.…”
Section: Resultsmentioning
confidence: 99%